Combination of HGF/MET-targeting agents and other therapeutic strategies in cancer. (April 2021) - Moosavi, Fatemeh; Giovannetti, Elisa; Peters, Godefridus J.; Firuzi, Omidreza
Highlights: Dysregulation of HGF/MET pathway is involved in tumorigenesis and drug resistance. Anti-HGF/MET agents are often combined with targeted or cytotoxic agents. Preclinical and clinical evidence of successful combinations are reviewed. Biomarkers are essential in selection of beneficial combinations. Abstract: MET receptor has emerged as a druggable target across several human cancers. Agents targeting MET and its ligand hepatocyte growth factor (HGF) including small molecules such as crizotinib, tivantinib and cabozantinib or antibodies including rilotumumab and onartuzumab have proven their values in different tumors. Recently, capmatinib was approved for treatment of metastatic lung cancer with MET exon 14 skipping. In this review, we critically examine the current evidence on how HGF/MET combination therapies may take advantage of synergistic effects, overcome primary or acquired drug resistance, target tumor microenvironment, modulate drug metabolism or tackle pharmacokinetic issues. Preclinical and clinical studies on the combination of HGF/MET-targeted agents with conventional chemotherapeutics or molecularly targeted treatments (including EGFR, VEGFR, HER2, RAF/MEK, and PI3K/Akt targeting agents) and also the value of biomarkers are examined. Our deeper understanding of molecular mechanisms underlying successful pharmacological combinations is crucial to find the best personalized treatment regimens for cancer patients.